Acceptability of Pre-Exposure Prophylaxis among Men Who Have Sex with Men and Transgender Women in Northern Thailand - Daniel Yang (2018)
Background:Northern Thailand has a high burden HIV epidemic among MSM and TG. Oral pre-exposure prophylaxis (PrEP) with tenofovir-emtricitabine has demonstrated efficacy in preventing HIV among MSM and TG in Chiang Mai, Thailand. Determinants of PrEP acceptability are needed to gauge the potential uptake of this prevention strategy.Methods:From January to February 2012, 238 MSM and TG participants, who self-reported as HIV-uninfected or of unknown status, completed a self-administered survey on hand-held computers. Participants were recruited by venue-day-time sampling and asked to rate their likelihood of using oral PrEP for HIV prevention with an efficacy of 50%. PrEP acceptability was defined as being "very likely" to use PrEP. Odds ratios and 95% CIs were calculated to identify correlates of acceptability.Results:131 MSM and 107 TG responded, with mean ages of 23.7 and 21.8, respectively. 24% of MSM engaged primarily in receptive anal sex vs. 74% of TG. 21% of MSM and 44% of TG reported regular medication use. Prior awareness of PrEP was high at 66% among both MSM and TG respondents. 41% of MSM and 37% of TG were "very likely" to use PrEP. Among MSM, factors associated with PrEP acceptability included a prior history of STIs (AOR 4.6; 95%CIs 1.7-12.6), previous HIV testing (AOR 2.4 95%CIs 1.1-5.3), regularly planned sex (AOR 2.8 95%CIs 1.1-7.2), and infrequent sex (AOR 2.9 95%CIs 1.3-6.3). Among TG, factors associated with acceptability included prior awareness of PrEP (AOR 3.3; 95%CIs 1.2-9.0) and having private insurance (AOR 5.0; 95%CIs 1.3-19.0).Conclusion:MSM and TG in Northern Thailand are distinct groups in terms of sexual behaviors, patterns of medication use, and correlates of PrEP acceptability. Efforts to maximize PrEP uptake should include expanded HIV testing services and the provision of financial subsidies to reduce the cost of PrEP. © 2013 Yang et al.